Effect of single dose alcohol administration on malondialdehyde, glutathione,total protein and hydroxproline levels of rat liver - Sibel DİNÇER,; Eser ÖZ,; Seren ÖZENİRLER, (Turkish Journal of Gastroenterology, 2019)
-